If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(6 + 5y) = 0 (6 * 3 + 5y * 3) = 0 (18 + 15y) = 0 Solving 18 + 15y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-18' to each side of the equation. 18 + -18 + 15y = 0 + -18 Combine like terms: 18 + -18 = 0 0 + 15y = 0 + -18 15y = 0 + -18 Combine like terms: 0 + -18 = -18 15y = -18 Divide each side by '15'. y = -1.2 Simplifying y = -1.2
| a^2-169=0 | | 10x+1=-9 | | 8senx-3=0 | | F(t)=-16t^2+45t+6 | | -8x-8+2x=-2x | | (180-x)+(90-x)=210 | | 3x^2-8x-340=0 | | (n-8)-(2n+2)= | | 15x-4=x-1 | | 3(-2m+5)=-4m+9-m | | 10+0.07(15x)+9=15x | | 3x+8(2x-6)=2+12x | | 10x^2+1000=0 | | 3y-4=4 | | (22x)(x)+8x+840=0 | | 11(7)-3=7(7)+25 | | 4x^2-5=43 | | 0.4x-1.2=0.15+1.8 | | 16+8m-4+2m=22 | | 10x+1000=0 | | 12x+60-28=9-12x | | 3x+8(2+6)=2+12x | | -6x+(-30)=24 | | 3y-0=4 | | 4x+20=7x-40 | | 10+4*a=3a | | -x-4+2x=2x+5-2x | | 16=x(2) | | 7+2(4x+2)+2x=20 | | 22x+8x+840=0 | | 1.1x+2.6=0.6x+1.25 | | 16=xsquared |